SISTEM KOMPENSASI DALAM BIDANG ASURANSI (STUDI KASUS PT. ASURANSI SINAR MAS MALANG) - Wulan; Arie Ambarwati (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2016)
Personnel wisdom is one of the important policies that must be considered in an effort to achieve the company's goals effectively and efficiently. After employees are recruited, selected and placed on a particular job, the company will focus its attention on the creation of a high performance, because high performance must be supported by high skills and knowledge as well as employees should have good attitude and behavior. Labor is a very important factor for the company, because everything related to the activities of the company is done by the workforce. In an effort to achieve the goals of the company depends on the willingness of its members to sacrifice and work hard. In order for it to be achieved there needs to be encouragement from the company as well as stimulant power so that employees can work hard and high work discipline. For that reason the problem of work responsibilities in relation to the policy of providing compensation should be given once, in order to improve employee performance in the company. The determination of compensation is one of the most important and complex tasks for the organization. To determine the compensation of the organization needs to pay attention to various aspects that affect the size and types of compensation to be applied in their organization. In addition to internal conditions, the determination of compensation is also influenced by an external environment filled with dynamics or change. The determination of compensation should be linked to the organization's business strategy and objectives to be achieved. According to Schuler and Jackson (1996) the problem often faced by the organization is how the compensation is determined in order to qualify for justice and fairness. Actual compensation not only satisfies the interests or needs of employees and organizations, but also the interests of society and government. Because the determination of compensation not only qualifies justice and fairness, it also meets regulations / laws, unions, and other factors. This study uses a qualitative approach by focusing on companies engaged in insurance. Characteristics of a typical insurance company provides its own model in setting compensation and compensation system. The number of types of insurance companies with various products offered to make researchers want to deepen the compensation system is implemented, as well as problems caused. The findings of the study classify that there are two models of compensation for insurance companies, namely the administrative model and the marketing model